Challenges for mountain hydrology in the third millennium - de Jong, Carmen (Frontiers in Environmental Science, 2015)
Mountain hydrology, in particular in the European Alps, has undergone significant changes within the last decades due to climate and land use change as well as altered water consumption patterns. Climate change influences both the characteristics of droughts and floods as well as evapotranspiration, snow-rainfall ratios, snow seasonality and water reserves locked in glaciers. Land use change and altered water use may strongly outweigh these impacts, in particular through industrialization, urbanization and tourism. Extreme hydrological situations such as new floods types have evolved from combined land-use and climate change and new types of water scarcity in association with accelerated and seasonally shifted water abstraction. Related water quality and pollution issues are of growing concern especially in seasonally highly populated areas. Main methodological challenges include keeping pace with recent hydrological change such as altered water inputs, water abstraction and water quality. Emphasis should be put on the significance of small proportional changes within the total water cycle as these may have major impacts on floods, water scarcity and general livelihood. Political challenges are strongest concerning problem reporting, initiation of monitoring programs and data transparency. The general lack of higher altitude hydrological data and experience with new hydrological phenomena will require an analytical approach directed more strongly towards interactions between scientists, stakeholders and decision makers encompassing local stakeholder knowledge and historical evidence. Data and innovative practices need to be exchanged more strongly between alpine regions and between the local and European level. It should be recognized that an alternative water management in mountains is fundamental for the future.